1988
DOI: 10.1161/01.cir.78.1.92
|View full text |Cite
|
Sign up to set email alerts
|

Long-term vasodilator therapy of chronic aortic insufficiency. A randomized double-blinded, placebo-controlled clinical trial.

Abstract: Although vasodilator drugs acutely reduce regurgitation and improve cardiac performance in aortic insufficiency, their long-term effects on left ventricular size and function are uncertain. Consequently, we performed a double-blinded, placebo-controlled trial using hydralazine in 80 minimally symptomatic patients who had clinically stable, moderate-to-severe aortic insufficiency. Patients randomized to hydralazine displayed a progressive reduction in left ventricular end-diastolic volume index (LVEDVI) measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(36 citation statements)
references
References 40 publications
1
34
1
Order By: Relevance
“…7,9 This is in contrast to clinical studies that have used hydralazine and achieved similar reductions in blood pressure but failed to offer the same clinical benefit as RAS inhibition. [48][49][50] In the present manuscript, we provide no explanation for this discrepancy. Taken together, these results suggest that blood pressure reduction may not be the sole factor influencing myocardial events such as fibrosis.…”
Section: Discussionmentioning
confidence: 60%
“…7,9 This is in contrast to clinical studies that have used hydralazine and achieved similar reductions in blood pressure but failed to offer the same clinical benefit as RAS inhibition. [48][49][50] In the present manuscript, we provide no explanation for this discrepancy. Taken together, these results suggest that blood pressure reduction may not be the sole factor influencing myocardial events such as fibrosis.…”
Section: Discussionmentioning
confidence: 60%
“…138 -141 Long-term treatment with a systemic vasodilator drug may be considered for those with severe aortic regurgitation who are deemed to be poor candidates for surgery. Several studies 142,143 have suggested that prolonged therapy with hydralazine and nifedipine in patients with severe aortic regurgitation and preserved LV function might act to minimize structural changes in the ventricle and thereby possibly delay the need for surgical intervention; however, these drugs are often poorly tolerated in this setting, and no trial has shown that these vasodilators can reduce the risk of HF or death (see ACC/AHA Guidelines for the Management of Patients With Valvular Heart Disease). 138 There are no long-term studies of vasodilator therapy in patients with severe asymptomatic mitral regurgitation.…”
Section: Patients With Severe Valvular Disease But No Symptomsmentioning
confidence: 99%
“…This analysis is subject to the usual limitations of comparisons of different clinical series with different patient selection factors and different end points. For example, 1 series 270 represents patients receiving placebo in a randomized drug trial 278 that included some patients with "early" New York Heart Association (NYHA) functional class II symptoms (although none had "limiting" symptoms), and another 272 represents patients receiving digoxin in a long-term study comparing the effects of nifedipine with digoxin. In 2 studies, 274,276 LV function was not reported in all patients, and it is unclear whether all had normal LV systolic function at baseline.…”
Section: Pathophysiologymentioning
confidence: 99%
“…304 -306,312 This is an inconsistent finding with a single oral dose of nifedipine. 308 -311 Reduced end-diastolic volume and increased ejection fraction have also been observed in small numbers of patients receiving long-term oral therapy with hydralazine and nifedipine for periods of 1 to 2 years 278,314 ; with nifedipine, these effects are associated with a reduction in LV mass. 272,314 Less consistent results have been reported with ACE inhibitors, depending on the degree of reduction in arterial pressure and end-diastolic volume.…”
Section: Diagnosis and Initial Evaluationmentioning
confidence: 99%